1995
DOI: 10.1111/j.1471-0528.1995.tb11404.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the induction to abortion interval in termination of second trimester pregnancies: a comparison of mifepristone with laminaria tent

Abstract: Objective To determine whether mifepristone (RU486) is more effective than laminaria tent in shortening the induction‐abortion interval in termination of second trimester pregnancies with gemeprost. Design Prospective randomised comparative trial. Setting Department of Obstetrics and Gynaecology in a University teachng hospital. Subjects Sixty‐two women undergoing termination of pregnancy in the second trimester. Interventions The women were allocated at random to one of the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…[17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins. None had significant side effects like pyrexia, nausea, vomiting and diarrhea probably due to lower dose of misoprostol.…”
Section: Discussionmentioning
confidence: 78%
“…[17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins. None had significant side effects like pyrexia, nausea, vomiting and diarrhea probably due to lower dose of misoprostol.…”
Section: Discussionmentioning
confidence: 78%
“…This process involves a hydrophilic organic substance, the most common of which being a seaweed of the species Laminaria digitata or Laminaria japonicum (or a synthetic counterpart of these materials) being placed within the cervix, after which, absorbing fluids and expanding over the course of several hours, thus dilating the cervix in the interim. In addition to the requirement of trained personnel to insert the tent, other disadvantages surrounding Laminaria tent usage include the potential risk of intrauterine tent displacement, cervical perforation and the fact that several tents may have to be inserted repeatedly to achieve the desired level of dilation, increasing the degree of associated discomfort [78]. Consequently, the incorporation of Cervidil ® may provide a safe and effective method of cervical dilation for reproductive tract surgeries.…”
Section: Projected Significance and Future Directions Of Studies On Hmentioning
confidence: 99%
“…Although this was an improvement over the oral misoprostol group (32 hours on average), it is still significantly longer than the 6-to 8-hour interval cited by other studies. 15,73,74 When used in combination with gemeprost, mifepristone significantly reduced both the induction-toabortion interval and the amount of gemeprost necessary to complete the induction. 72 In this study, in which women 14 to 20 weeks gestation (n ¼ 62) were randomly assigned to pretreatment with mifepristone 600 mg or laminaria tent before prostaglandin treatment, side effects were similar between the two groups.…”
Section: Mifepristone For Second-trimester Abortionmentioning
confidence: 99%